Design and Implementation of a Bluetooth-Based Rover Prototype for Short Range Extraterrestrial Explorations. An Exploratory Study - Byakatonda , Denis; Kamya, Willy (Student’s Journal of Health Research Africa, 2022)
Background: Extraterrestrial exploration is an integral part of scientific research, some unnavigable or hard-to-reach places such as active volcanoes, bottoms of water bodies, radioactive sites and experimental chambers, mountain caves, or even other planets may contain very valuable data about our universe or some scientific phenomena. This project attempted to solve some of these accessibility problems by designing and implementing a rover that could be used to explore such environments without putting human life at stake. Methodology: The project adopts a very cost-effective approach, firstly, Arduino boards and Atmega microcontrollers are used for the design of control systems, and Bluetooth is used for remote communication. Performance results showed that the Bluetooth technology is suitable for use in a clean environment with fewer obstacles, the HC-05 Bluetooth was able to receive and transmit data up to 8 meters in a clear environment and up to 2.5 meters through walls. Results: Furthermore, the rover was 86.7% accurate in detecting obstacles along its way using ultrasonic sound sensors. The testing results are in the range of agreement with those of similar projects such as the obstacle avoidance robotic car by Bilkis, Faiza, Susmita & Muhammad (2017). Conclusion: The results of the study showed that building exploration robots or rovers can be built using cost-effective contemporary technology that is accessible to most developers, implementation of an obstacle is possible with Ultrasonic sensors and short to midrange communication and control is possible via Bluetooth. Recommendation: However, future researchers may investigate the use of renewable energy in powering the rovers and improving the transmission quality of Bluetooth.